Structural and molecular basis of PCNA-activated FAN1 nuclease function in DNA repair - F. Li; A. S. Phadte; M. Bhatia; S. Barndt; A. R. Monte Carlo III; C-F. D. Hou; R. Yang; S. Strock; A. Pluciennik (Nature Communications)
Abstract FAN1 is a DNA dependent nuclease whose proper function is essential for maintaining human health. For example, a genetic variant in FAN1, Arg507 to His hastens onset of Huntington’s disease, a repeat expansion disorder for which there is no cure. How the Arg507His mutation affects FAN1 structure and enzymatic function is unknown. Using cryo-EM and biochemistry, we have discovered that FAN1 arginine 507 is critical for its interaction with PCNA, and mutation of Arg507 to His attenuates assembly of the FAN1–PCNA complex on a disease-relevant extrahelical DNA extrusions formed within DNA repeats. This mutation concomitantly abolishes PCNA–FAN1–dependent cleavage of such extrusions, thus unraveling the molecular basis for a specific mutation in FAN1 that dramatically hastens the onset of Huntington’s disease. These results underscore the importance of PCNA to the genome stabilizing function of FAN1.